Native language interference in learning english as foreign language: an analysis of written material produced by spanish speaking students in senior high school classes. - Rodríguez, Patricia (2010)
In view of the fact that Spanish interference is a real aspect present in learning english as a second language, it was essential to make further investigation and determine the most common grammatical and lexical errors product of spanish language intervention. While the research has been taking place, it was established that one of the most common problems made by learners is the transfer of L1 into L2; it is not the most appropriate resource that learners must overcome at the moment of EFL writing; which produces interference and becomes an inappropriate tool to use it at english language learning.